2015
DOI: 10.1039/c4nr05128a
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption of a binary CO2–CH4mixture in nanoporous carbons: effects of edge-functionalization

Abstract: The effect of edge-functionalization on the competitive adsorption of a binary CO2-CH4 mixture in nanoporous carbons (NPCs) has been investigated for the first time by combining density functional theory (DFT) and grand canonical Monte Carlo (GCMC) simulation. Our results show that edge-functionalization has a more positive effect on the single-component adsorption of CO2 than CH4, therefore significantly enhancing the selectivity of CO2 over CH4, in the order of NH2-NPC > COOH-NPC > OH-NPC > H-NPC > NPC at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 68 publications
13
110
0
1
Order By: Relevance
“…To carry out the detailed adsorption orientations of CO 2 and N 2 molecules on calcite pore surface, the angle θ , formed between the axial direction of the gas molecule and the pore surface, was quantified to perform the adsorption orientations of CO 2 and N 2 adsorbed onto the pore surface as shown in Figure . It is found that, the CO 2 molecules adsorbed close onto the calcite pore surface have the θ of ∼30°–∼70° (∼110°–∼150°), because the CO 2 molecules have strong adsorption tendency by the O atom toward to the positive charge position of Ca 2+ ions of the pore surface . While for N 2 , the θ is in a wide range, which indicates that no specific adsorption orientation are exist for N 2 molecules adsorbed onto the calcite surface, it is also consistent with that mentioned above, the N 2 molecules have weak adsorption interactions with the calcite pore surface.…”
Section: Resultssupporting
confidence: 76%
“…To carry out the detailed adsorption orientations of CO 2 and N 2 molecules on calcite pore surface, the angle θ , formed between the axial direction of the gas molecule and the pore surface, was quantified to perform the adsorption orientations of CO 2 and N 2 adsorbed onto the pore surface as shown in Figure . It is found that, the CO 2 molecules adsorbed close onto the calcite pore surface have the θ of ∼30°–∼70° (∼110°–∼150°), because the CO 2 molecules have strong adsorption tendency by the O atom toward to the positive charge position of Ca 2+ ions of the pore surface . While for N 2 , the θ is in a wide range, which indicates that no specific adsorption orientation are exist for N 2 molecules adsorbed onto the calcite surface, it is also consistent with that mentioned above, the N 2 molecules have weak adsorption interactions with the calcite pore surface.…”
Section: Resultssupporting
confidence: 76%
“…For CH 4 , the gas molecule is trapped in the concave sites of the pore surface. This is because, in contrast to CO 2 , the CH 4 molecule is tetrahedral with a C atom in the center surrounded by four H atoms, which are repelled by the H atoms of the surface hydroxyl groups, hence the interactions between CH 4 molecules and the pore surface are much weaker than those of CO 2 (Table ). Therefore, the rough surface plays another factor in addition to the adsorption interactions between the gas molecule and the pore surface.…”
Section: Resultsmentioning
confidence: 99%
“…Weniger et al showed that as the increase of vitrinite content, the amount of adsorbed carbon dioxide decreases significantly, while the amount of adsorbed methane remains unchanged (Figure ). Lu et al studied binary gas adsorption on nanoporous carbon with different functional groups . It was found that the difference of molecular functional groups significantly affects the selectivity factor.…”
Section: Factors Affecting the Adsorption Of Tcgmentioning
confidence: 99%